ON BIPARTITE EDGE FRUSTRATION OF CARBON AND BORON NANOTUBES - HAYAT, Sakander; SIDDIQUI, Hafiz Muhammad Afzal (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The measure of bipartivity is one of the important topological and structural property which describes the chemical stability of underlying chemical structures. Bipartite edge frustration is one of the topological descriptors which calculate measure of bipartivity of a chemical structure. Carbon hexagonal nanotubes, boron triangular nanotubes and boron -nanotubes are important nanostructures, which have been studied extensively by both of the theoretical and computational chemists. In this article, we consider carbon hexagonal nanotubes, boron triangular nanotubes and boron -nanotubes for the study of bipartite edge frustration.